Brocchia cinerea (Delile) Vis. Essential Oil Antimicrobial Activity and Crop Protection against Cowpea Weevil Callosobruchus maculatus (Fab.) - Abdelkrim Agour; Ibrahim Mssillou; Hamza Mechchate; Imane Es-safi; Aimad Allali; Azeddin El Barnossi; Omkulthom Al Kamaly; Samar Zuhair Alshawwa; Abdelfattah El Moussaoui; Amina Bari; Badiaa Lyoussi; Elhoussine Derwich (Plants, 2022)
Antibiotics and synthetic pesticides are now playing a role in the spread of resistant pathogens. They continue to have negative consequences for animal and plant health. The goal of this work is to identify the chemical composition of Brocchia cinerea (Delile) Vis. essential oil (EO) using GC-MS(Gas Chromatography-Mass Spectrometer), evaluate its antimicrobial properties, and investigate its insecticidal and repellent effectiveness against Callosobruchus maculatus (C. maculatus). The GC-MS indicated the presence of 21 chemicals, with thujone (24.9%), lyratyl acetate (24.32%), camphor (13.55%), and 1,8-cineole (10.81%) being the most prominent. For the antimicrobial assay, the yeast Candida albicans was very sensitive to the EO with a growth inhibition diameter of (42.33 mm), followed by Staphylococcus aureus (31.33 mm). Fusarium oxysporum is the mycelia strain that appeared to be extremely sensitive to the utilized EO (88.44%) compared to the two species of Aspergillus (A. flavus (48.44%); A. niger (36.55%)). The results obtained in the microdilution method show that Pseudomonas aeruginosa was very sensitive to the EO, inhibited by a very low dose (0.0018 mg/mL). The minimum inhibitory concentration (MIC) results were between 0.0149 and 0.06 mg/mL. B. cinerea EO also demonstrated a potent insecticidal effect and a medium repulsive effect against C. maculatus. Thus, the LC50 value in the contact test was 0.61 μL/L of air, lower than that observed in the inhalation test (0.72 μL/L of air). The present study reveals that B. cinerea EO has the potential to be an antimicrobial and insecticidal agent with a better performance against several pathogenic microorganisms.